Design and Build a Child's Learning Room Application, in Increasing Learning Motivation Based on Android - Antonius Yadi Kuntoro; Hermanto Hermanto (Institute of Computer Science (IOCS), 2020)
Millennials are often associated with the term “kids zaman now” or